Complex effects of international relations intended and unintended consequences of human actions in the Middle East - Israeli, Ofer (SUNY series, James N. Rosenau series in global politics, 2020)
"Identifies the many ways in which unexpected outcomes are endemic to international relations due to the complexity of world politics"--